Understanding Rett Syndrome: Genetic, clinical and therapeutic perspectives - literature review - Urbańska, Sylwia; Witas, Aleksandra; Borowska-Łygan, Martyna; Pięta, Justyna (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Rett syndrome (RTT) is a genetic neurodevelopmental disorder that predominantly affects the female. The disease develops after 6 months of age causing abnormalities in the child's development. The aim of this article is to bring together the latest information and clinical, genetic and therapeutic perspectives on RTT. Review Methods: The review was based on publicly available PubMed and Google Scholar, Web of Science and Scopus databases from 2019 to 2024 using the following phrases: rett syndrome, rett syndrome treatment, rett syndrome rehabilitation, MECP2. Publications were analyzed using a non-systematic review method to create a brief synthesis of the available information. Brief Description of the State of Knowledge: Rett syndrome is characterised by a loss-of-function mutation in the MECP2 gene, which is located on the long arm of the X chromosome. The diagnosis is confirmed by clinical criteria such as complete loss of acquired targeted hand skills, spoken language, gait abnormalities and confirmation of the mutation in the MECP2 gene. Treatment focuses on multidisciplinary management of the symptoms associated with the disease and an individualised rehabilitation programme. Recent studies show positive effects of trofinetide treatment, and gene therapy, genome editing and ataluren promise to be a promising treatment for RTT. Summary: The authors highlight the need for development of early diagnosis of RTT in infants, rehabilitation focused on family-centred care (FCC) and the need for further research towards innovative treatments for Rett Syndrome.